Social Interaction in Petamburan as a Form of Socio-Religious Tolerance in Indonesia - Abdillah, Aldi; Maringan Hasiholan, Anggi; Sandra Sumual, Ivonne; Jordi Ibrani, Allen; Steven, Josua (KnE Social Sciences, 2022)
Petamburan is a sub-district of Jakarta, Indonesia’s capital city, and it has been a center of attention in Indonesia because of the growth and movement of the Islamic Front Defenders (Front Pembela Islam: FPI) within it. Before the FPI was officially banned by the Indonesian government on December 30, 2020, all of its activities and controversies performed in the name of Islam and its leader had become a main attraction for Indonesia’s mainstream media. This impacts Petamburan, which is described as a conflict-prone area in terms of social and religious factors. However, the image of Petamburan from the mass media does not describe the depth of its social reality. This research proposed a core hypothesis that the Petamburan people have deep riches of social harmony in terms of religion, race, and social factors. This study used a social interaction approach and analysis that focused on interactions in the actual public spheres in Petamburan. The final result was a picture of social and religious tolerance from the wide social diversity in the Petamburan community as a form of harmonious and inclusive social life in Indonesia. Keywords: social interaction, religion, public sphere, virtual space, FPI